The Impact of Voluntary and Involuntary Intellectual Capital Disclosure on Firm Value - Anin Dyah Luthfiani; Ani Wilujeng Suryani (The Indonesian Journal of Accounting Research, 2022)
The digital era has changes corporate asset structures and business models, and it requires companies to have more value-added resources to be more competitive, one of which is intellectual capital. Prior studies have analyzed the intellectual capital disclosure in annual reports. This approach, however, is unable to identify the depth of intellectual capital information. This study builds on previous studies using the involuntary disclosure concept to examine how information created by stakeholders and other parties outside of management may affect a company’s reputation. In addition to annual reports, this study also measures intellectual capital disclosure information using new data sources such as social media and online business media. This study aims to examine the impact of voluntary and involuntary disclosure of intellectual capital on a firm's value. The sample of this study consisted of 32 banks listed on the Indonesia Stock Exchange in 2019. The results of the study indicate that intellectual capital disclosure affects the firm value. These findings provide a practical implication for managers to disclose intellectual capitals that are relevant to the market’s demands and focus on the quality of the information to increase firm value and sustain in a competitive environment.